IMPROVING THE EFFICIENT MANAGEMENT STRATEGY OF ECONOMIC SUBJECTS UNDER THE DEFICIT OF FINANCIAL RESOURCES (Scientific electronic journal "Labor Economics and Human Capital", 2024)
This article highlights one of the most pressing issues faced by business entities - the problem of a shortage of financial resources. In particular, the issues of how to properly manage an enterprise in such a situation and how to organize production were considered. The enterprise conducted a theoretical analysis of how to prevent the occurrence of a shortage of financial resources, be able to correctly predict it and rationally assess the risks associated with it. Recommendations are given for determining practical measures that are advisable to take in the conditions of a shortage of financial resources.
Keywords: deficit of financial resources, financial management, cash flow, compulsory payment, inflation, strategic plan, corporate management, cost efficiency, hidden risk, targeted cash reserves, social protection, emergency payments.